Pelatihan Penerapan Kebijakan Akuntansi Pemerintah Daerah Sesuai PP 71/2010 dan PP 12/2019 di Kabupaten Rokan Hilir - Azlina, Nur; Desmiyawati, Desmiyawati; Mukhlisin, Mukhlisin (Komunitas Manajemen Kompetitif, 2021)
This Community Service activity aims to provide assistance in the form of training for regional financial administration staff who compile financial reports at OPD (Regional Government Organization) Rokan Hilir Regency. This method of community service activities is by providing modules, concept explanations as well as discussion and question and answer about accounting policies used in the preparation of accrual-based financial reports in the Rokan Hilir Government to employees assigned to Regional Government Organizations (OPD) of Rokan Hilir Regency. It is hoped that the implementation of this service is so that the revised accounting policies run effectively, and improve the understanding of accounting administration staff in the Rokan Hilir government regarding these accounting policies in order to prepare local government financial reports in accordance with PP No. 71 of 2010 and PP No.12 of 2019. Keywords: Regional Government Accounting Policies, PP 71/2010, PP 12/2019, Rokan Hilir Regency